A new species of Neochrysocharis Kurdjumov (Hymenoptera: Eulophidae), a parasitoid of serpentine leafminers (Diptera: Agromyzidae) in Southeast Asia - Fisher, Nicole; la Salle, John (Zootaxa, 2005)
Neochrysocharis beasleyi sp.n. (Hymenoptera: Eulophidae: Entedoninae) is described from Indonesia and Vietnam. This species is a parasitoid of leafmining Agromyzidae, and is a potential biological control agent for invasive agromyzid species. Variation within Southeast Asian specimens of Neochrysocharis formosa is described and discussed. Neochrysocharis stat. rev. is treated as a valid genus, and removed from synonymy with Closterocerus.Key words: Hymenoptera, Eulophidae, Neochrysocharis, parasitoids, Agromyzidae, Liriomyza, Indonesia, Vietnam, Neochrysocharis formosa, variation